Chirality transfer in mandelate ionic liquids through ion pairing effects - Sachnov, Swetlana; Schneiders, Karola; Schulz, Peter; Wasserscheid, Peter (Tetrahedron-Asymmetry, 2010)
Ion pairing in [N-(3′-oxohexyl)-N-methylimidazolium][(R)-mandelate] was probed as a function of its concentration in ethanol and compared to the corresponding [(S)-camphorsulfonate] ionic liquid. The applied methodologies comprised asymmetric hydrogenation with ee monitoring as well as independent diffusion-ordered NMR and conductivity measurements.